Collaboration in continuing education networks: option or destiny? - Alfredo Soeiro (2001)
The demand for the provision of different forms and types of Continuing Education has shown a tremendous increase in the last years. There have been difficulties and obstacles to the transformation of the university classical structure and of the typical activities of the academic staff. Several models of managing Continuing Education in the universities were developed, tested and implemented. A reaction of the universities to the transformations created by the need for lifelong learning demands has been the cooperation in projects or in agreements that can be bilateral or multilateral. These multilateral agreements take most of the times the form of networks rising from several projects that have been implemented or from natural aggregation of universities around a common ground. The experiences of benchmarking around this theme are presented.